Effect of Synthesis Conditions on the Morphology of Polyaniline - Aleahmad, Mahdi; Ghafouri Taleghani, Hamidreza; Eisazadeh, Hossein (Asian Journal of Chemistry, 2010)
Polyaniline was prepared in aqueous medium by using various synthesis conditions. The polyaniline nanoparticles were characterized in terms of their morphology, particle size, conductivity and chemical structure. The results indicate that the morphology, particle size and conductivity of nanoparticles are dependent the synthesis conditions. The chemical structure of the products was determined by FTIR spectroscopy.